IDENTIFYING VALUES OF RELIGIOUS MODERATION THROUGH LEARNING ACTIVITIES - Mahsusi Mahsusi; Syihaabul Hudaa; Nuryani Nuryani; Ahmad Bahtiar; Makyun Subuki (Balai Penelitian dan Pengembangan Agama Makassar, 2023)
Religious intolerance is a significant problem in Indonesia. This concern arises along with offline learning activities. Students who were previously limited in their activities can now move freely on campus. The lack of insight into religious tolerance causes new individuals to become intolerant easily. The purpose of this article is to explain how to implement the values of religious tolerance through compulsory general Indonesian language courses. This research belongs to the descriptive qualitative type using a direct-action research approach. The stages of this research were carried out with the introduction of Indonesian language courses, the provision of semester learning plans, discussion of materials 1-13, and the implementation of religious moderation in short writing production material. The discovery learning model used is Jerome Bruner's theory. The media used as an analysis material is the Tanda Tanya film directed by Hanung Bramantyo. Respondents in this study were 105 people taken from various scientific backgrounds at UIN Syarif Hidayatullah Jakarta. Random sampling aims to get natural results without any assumption of data manipulation and selection of data sources. This research was conducted in two stages, including first data collection, evaluation, and second data collection. It was found that the students of UIN Syarif Hidayatullah Jakarta were able to find moderation values in the Tanda Tanya film. A total of 78 students have been able to analyze the meaning of religious moderation. Then, 14 students understood the meaning of moderation contained in the film through the discovery learning model.